Reducing Diesel Engine Drive Cycle Fuel Consumption through Use of Cylinder Deactivation to Maintain Aftertreatment Component Temperature during Idle and Low Load Operating Conditions - Joshi, Mrunal C.; Gosala, Dheeraj B.; Allen, Cody M.; Vos, Kalen; Van Voorhis, Matthew; Taylor, Alexander; Shaver, Gregory M.; McCarthy, James; Stretch, Dale; Koeberlein, Edward; Farrell, Lisa (Frontiers in Mechanical Engineering, 2017)
Modern on-road diesel engine systems incorporate flexible fuel injection, variable geometry turbocharging, high pressure exhaust gas recirculation, oxidation catalysts, particulate filters and selective catalytic reduction systems in order to comply with strict tailpipe-out NOx and soot limits. Fuel consuming strategies, including late injections and turbine-based engine exhaust throttling are typically used to increase turbine outlet temperature and flow rate in order to reach the aftertreatment component temperatures required for efficient reduction of NOx and soot. The same strategies are used at low load operating conditions to maintain aftertreatment temperatures. This paper demonstrates that cylinder deactivation (CDA) can be used to maintain aftertreatment temperatures in a more fuel efficient manner through reductions in airflow and pumping work. The incorporation of CDA to maintain desired aftertreatment temperatures during idle conditions is experimentally demonstrated to result in fuel savings of 3.0% over the HD-FTP drive cycle. Implementation of CDA at non-idle portions of the HD-FTP where BMEP is below 3 bar is demonstrated to reduce fuel consumption further by an additional 0.4%, thereby resulting in 3.4% fuel savings over the drive cycle.